2019
DOI: 10.1039/c9na00501c
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the nanosize effect of carbon nanomaterials on the dehydrogenation temperature of ammonia borane

Abstract: This study aims to clarify the correlation between the particle size of ammonia borane and the H2 desorption temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…First, Tang et al [261] clearly showed that nanoparticles with a diameter of 4 nm were able to dehydrogenate starting from 50 °C, whereas larger nanoparticles (diameter of 10 nm) dehydrogenated from 67 °C. So et al [262] showed that the dehydrogenation of ammonia borane Third, the ammonia borane nanophase is amorphous and, accordingly, it has an altered dihydrogen N−H δ+ •••H δ− −B network [253], and more mobile and active molecules [174].…”
Section: Nanoconfinement Of Ammonia Boranementioning
confidence: 99%
See 1 more Smart Citation
“…First, Tang et al [261] clearly showed that nanoparticles with a diameter of 4 nm were able to dehydrogenate starting from 50 °C, whereas larger nanoparticles (diameter of 10 nm) dehydrogenated from 67 °C. So et al [262] showed that the dehydrogenation of ammonia borane Third, the ammonia borane nanophase is amorphous and, accordingly, it has an altered dihydrogen N−H δ+ •••H δ− −B network [253], and more mobile and active molecules [174].…”
Section: Nanoconfinement Of Ammonia Boranementioning
confidence: 99%
“…The positive effects described for the silica scaffolds are valid for the carbon scaffolds (Figure 15). First, Tang et al [261] clearly showed that nanoparticles with a diameter of 4 nm were able to dehydrogenate starting from 50 • C, whereas larger nanoparticles (diameter of 10 nm) dehydrogenated from 67 • C. So et al [262] showed that the dehydrogenation of ammonia borane could be tuned by controlling the scaffold pore size in such a way that the narrower the pore size is, the lower the peak temperature of the H 2 release. In other words, microporosity (a pore size of <2 nm) should be favored [263].…”
Section: Nanoconfinement Of Ammonia Boranementioning
confidence: 99%
“…NaBH4 [49,74,216,236,241], Mg(BH4)2 [42,55,61,70,105,126,132,151,159,207,216,220,224,236,242,243], Ca(BH4)2 [116,216,236,243] and (TM)(BH4)x [150,216], ammonia-borane NH3.BH3 [36,38,63,64,75,85,86,88,90,139,[140][141][142][143][144]153,154,156,162,171,175,197,213,[244]…”
Section: Tm-hydridesmentioning
confidence: 99%
“…Other details about the infiltration method; the onset dehydrogenation temperature, T onset ; the peak at which H 2 is released, T peak ; the activation energy, E a ; and the byproducts detected from the sample are given, when available. [278] used different carbons with different pore size distribution to confine AB. They found that carbon with pores of about 0.4 nm presented the best performance in their study.…”
Section: Silicon-based Scaffoldsmentioning
confidence: 99%